Effective medium theory for the thermoelectric properties of composite materials with various percolation thresholds - Snarskii, A.O.; Yuskevich, P. (Journal of Thermoelectricity, 2019)
In the work, a modified effective medium theory is constructed for calculating the effective properties of thermoelectric composites with different values of percolation thresholds. It is shown that even at concentrations beyond the critical region, the threshold value is essential for determining the effective properties. Two fundamentally different cases of a set of local properties of the composite are considered. In one of these cases, the conductivity and thermal conductivity of one of the phases is simultaneously greater than the conductivity and thermal conductivity of the other phase. The second, anomalous case, when the electrical conductivity of the first phase (σ1) is greater than that of the second, but the thermal conductivity of the first phase is less than that of the second, shows unusual concentration behavior of effective conductivity, i.e. with an increase in the well-conducting phase, the effective conductivity σе shows a decrease (rather than growth as in the standard case, see Fig. 1a), which at p ≈ pc goes over to growth. Bibl. 5, Fig. 5.